Characterization of dairy milk microbiota: implications of streptococcus parauberis for food safety and Ralstonia pickettii as a pathogen in subclinical mastitis - Rifa’i Rifa’i; Puguh Surjowardojo; Lilik Eka Radiati; La Choviya Hawa (CyTA - Journal of Food)
This study aimed to characterize the microbiota of fresh cow’s milk and milk from cows with early-stage subclinical mastitis (CMT score 1) using 16S rRNA sequencing via Oxford Nanopore Technologies. DNA was extracted from milk samples collected from smallholder dairy farms and taxonomically classified to identify dominant bacterial species. Streptococcus parauberis was predominant in fresh milk, indicating its dual role in fermentation and as a potential marker for early mastitis. Conversely, Ralstonia pickettii was dominant in mastitis-affected milk, supporting its role as an emerging pathogen. These microbial shifts may impact milk quality and safety. The findings underscore the utility of nanopore-based metagenomics for microbial profiling in raw milk and its potential in early mastitis detection and food safety monitoring in dairy production systems.